Evaluation of Bioequivalence of Generic Imatinib Products and Generic Tacrolimus Products Based on Indirect Comparison of the Results of Their Bioequivalence Studies - D. V. Goryachev; N. E. Uvarova (Регуляторные исследования и экспертиза лекарственных средств, 2019)
Generic drugs are widely discussed in the scientific literature. Their key advantage is high availability in the medical practice due to the possibility of a significant reduction in developer costs. In most cases the efficacy and safety of generic oral drugs are confirmed based on the acceptable results of pharmacokinetic evaluation of their bioequivalence with the reference drug. However, generic drugs are not directly compared with one another, and this calls into question the validity of the conclusion about the interchangeability of the generic drugs.The aim of this study was to evaluate the results of indirect comparison of generic drugs by the ratios of their AUC0-t and Сmax based on the information obtained in bioequivalence studies involving the reference drug.Materials and methods: the authors performed an indirect comparison of the results of bioequivalence studies of generic drugs containing one active pharmaceutical ingredient. The analysis was based on bioequivalence study reports over the last 7 years dealing with risk/benefit assessment of imatinib and tacrolimus products.Results: the results of indirect assessment of 90 % confidence intervals of the ratios of imatinib products’ geometric means show that in 46.7 % of cases the intervals fall outside the generally accepted limits (80–125 %) for at least one of the estimated parameters. As for tacrolimus products, the intervals did not go beyond the generally accepted limits (80–125 %) for the AUC0-t  ratio, but a discrepancy was found in 10 % of cases for the Cmax ratio. However, when narrower limits of 90–111 % were used to assess the AUC0-t ratio, 90 % of the compared pairs did not meet the recommended standards. Conclusions: thus, conclusions on the acceptable degree of bioequivalence of two generic drugs to the reference product cannot constitute a scientifically sufficient reason for regarding these generic drugs as clinically equivalent.